2009
DOI: 10.1007/s10509-009-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Artificial contradiction between cosmology and particle physics: the Λ problem

Abstract: Abstract. It is shown that the usual choice of units obtained by taking G = c = ђ = 1, giving the Planck‚s units of mass, length and time, introduces an artificial contradiction between cosmology and particle physics: the lambda problem that we associate with ђ. We note that the choice of ђ = 1 does not correspond to the scale of quantum physics. For this scale we prove that the correct value is ђ ≈ 1/10 122 , while the choice of ђ = 1 corresponds to the cosmological scale. This is due to the scale factor of 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…At this point it might be helpful to underline that given that the above recurrent picture is realized in Nature, supports the interest of the ideas argued in Ref. (37), about the connections between the cosmological constant and the quantum behavior of matter in such internal universes. An important outcome emerged in the examination of the problem, is that the coexistence of the scalar field as described by the EKG equations including also the dust energy momentum tensor does not allow the existence of static solutions, at least in centrally symmetric configurations, in the absence of Dilaton -matter interaction (26).…”
Section: A) Small Mass Dilatonsupporting
confidence: 58%
“…At this point it might be helpful to underline that given that the above recurrent picture is realized in Nature, supports the interest of the ideas argued in Ref. (37), about the connections between the cosmological constant and the quantum behavior of matter in such internal universes. An important outcome emerged in the examination of the problem, is that the coexistence of the scalar field as described by the EKG equations including also the dust energy momentum tensor does not allow the existence of static solutions, at least in centrally symmetric configurations, in the absence of Dilaton -matter interaction (26).…”
Section: A) Small Mass Dilatonsupporting
confidence: 58%
“…This is well in the range of observations [3]. The Hubble radius for today is defined as c/H(t 0 ) ≈ c t 0 and taking this radius as the present reference for the cosmological scale factor, i.e., c t 0 ≈ R(1) we get from (6), (7) and (8) to first order…”
mentioning
confidence: 54%
“…It may be linked to the entropy of the universe (with Boltzmann constant k = 1). It is also the order of magnitude of the discrepancy between the values of the cosmological constant Λ, as derived from cosmological information, and from the standard particle theory [7].…”
mentioning
confidence: 99%
“…From the assumed (as an angular momentum) and observed constancy of the Planck´s constant ђ (radioactive decay times depend on the 7 th power of ђ, and no time variation in these times has been observed) and (4) one has to assume also that the electronic charge e is a true constant. We have shown elsewhere, Alfonso-Faus [6], that the Planck´s constant for the quantum world is of the order of 1/10 122 . We also showed that this constant is the square of the length of the scale, in a system of units that we adopt in part given by the equality G = c 3 .…”
Section: -The Cosmological Quantum Of Electrical Chargementioning
confidence: 82%
“…If we take now as the cosmological unit of length the size of the universe ct ≈ 10 28 cm, the cosmological "quantum" of length, then Planck´s constant for the quantum world is the square of the ratio of ct to the Planck´s unit of length L = ct ≈ 10 28 cm = 1 ђ ≡ (ct) 2 c 3 /Gђ ≈ 1/10 122 (6) and from (1), (2) and (6) we get for the cosmological quantum of electrical charge Q ≈ 3.3 10 61 e = 1 (7) This is the same value as has been obtained elsewhere, Alfonso-Faus [7], where we have found equilibrium in the plasma state of the universe with charge (7) pushing outwards against the inward gravitational force. The Debye length of this plasma is a bit larger than the size L in (6). We see that the number of electronic charges in (7) is the same as the number of Planck´s units that could make up for the universe (with a dimensionless scale factor of ∼ 10 61 ).…”
Section: -The Cosmological Quantum Of Electrical Chargementioning
confidence: 99%